Since time immemorial : Native custom and law in colonial Mexico - Yannakakis, Yanna, 1967- (Duke University Press, 2023)
"In Since Time Immemorial Yanna Yannakakis traces the invention of Native custom, a legal category that Indigenous litigants used in disputes over marriage, self-governance, land, and labor in colonial Mexico. She outlines how in the hands of Native litigants, the European category of custom-social practice that through time takes on the normative power of law-acquired local meaning and changed over time. Yannakakis analyzes sources ranging from missionary and Inquisition records to Native pictorial histories, royal surveys, and Spanish and Native-language court and notarial documents. By encompassing historical actors who have been traditionally marginalized from legal histories and highlighting spaces outside the courts like Native communities, parishes, and missionary schools, she shows how imperial legal orders were not just imposed from above but also built on the ground through translation and implementation of legal concepts and procedures. Yannakakis argues that ultimately, Indigenous claims to custom, which on the surface aimed to conserve the past, provided a means to contend with historical change and produce new rights for the future"--